2021
DOI: 10.1002/asl.1073
|View full text |Cite
|
Sign up to set email alerts
|

Improved representation of atmospheric dynamics in CMIP6 models removes climate sensitivity dependence on Hadley cell climatological extent

Abstract: The persistent inter‐model spread in the response of global‐mean surface temperature to increased CO2 (known as the “Equilibrium Climate Sensitivity,” or “ECS”) is a crucial problem across model generations. This work examines the influence of the models' present‐day atmospheric circulation climatologies, and the accompanying climatological cloud radiative effects, in explaining that spread. We analyze the Coupled Model Intercomparison Project Phase 6 (CMIP6) models and find that they simulate a more poleward,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Investigating the Hadley cell (HC) extents in both CMIP6 and CMIP5 GCMs, De et al . (2022) surmised that CMIP6 GCMs simulate large‐scale atmospheric dynamics closer to the observations compared to CMIP5 GCMs.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Investigating the Hadley cell (HC) extents in both CMIP6 and CMIP5 GCMs, De et al . (2022) surmised that CMIP6 GCMs simulate large‐scale atmospheric dynamics closer to the observations compared to CMIP5 GCMs.…”
Section: Introductionmentioning
confidence: 92%
“…Interestingly, the study executed by Bock et al (2020) and Xin et al (2020) demonstrated that CMIP6 GCMs were more capable of reproducing the observed mean precipitation and surface temperature pattern compared to CMIP3 and CMIP5 GCMs, on a global scale and continental (East Asia) scale, respectively. Investigating the Hadley cell (HC) extents in both CMIP6 and CMIP5 GCMs, De et al (2022) surmised that CMIP6 GCMs simulate large-scale atmospheric dynamics closer to the observations compared to CMIP5 GCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Our main goal is to identify and compare the uncertainties and differences in CMIP6 projections of California rainfall to those of CMIP5, and point to possible underlying mechanisms. Generally, CMIP6 models have gone through multiple improvements, including better representation of clouds and aerosols (Zelinka et al, 2020), and better representation of atmospheric and jet dynamics, especially in the Southern Hemisphere, due to increased horizontal grid resolution (Curtis et al, 2020; De et al, 2022; di Luca et al, 2020), more detailed stratospheric processes (Eyring et al, 2016), and more accurate incorporation of volcanic forcing during the historical period (Zanchettin et al, 2016). In addition, the CMIP6 ensemble has reduced biases of tropical and subtropical precipitation relative to the observations for the historical simulations as compared to CMIP5, mainly due to the inclusion of falling ice radiative effects (FIREs) in some of the models (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Important enhancements were made to the CMIP6 Global Climate Models (GCMs) leading to an overall better performance than previous CMIP generations as documented by e.g. Fan et al (2020); Brands (2022a), and a higher global climate sensitivity (Zelinka et al, 2020;De et al, 2022). The IPCC (2023) even states that "robust climate information is increasingly available at regional scales for impact and risk assessments", indicating that GCMs are becoming sufficiently advanced to be used for decision-making on a regional scale.…”
Section: Introductionmentioning
confidence: 99%